Peningkatan Mutu Sekolah Dasar di Era Otonomi Daerah - Achmad Habib (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2007)
Abstract: The condition of basic educational institutions in local area are mostly not very outstanding. They still face so many problems, such as: minimal facilities, low standard of teacher’s quality, lack of funding and many other problems. The effort of local governments to help solving the problems proved to be unsuccessful. This article tries to identify the Elementary School problems and to find some strategies to cope with those problems. In conclusion, the role of Elementary School master is so important to have some smart strategies to develop their school environment and strengthen their team work. For this tough job, they should master the art of management, so that they will able to cope with solving those complicated problems in their each schools.